Exclusive and dual influenza and COVID-19 vaccination among U.S. adults and adolescents in 2021. (12th December 2023) - Nguyen, Kimberly H.; Zhao, Ruitong; Chen, Siyu; Bednarczyk, Robert A.
Abstract: Introduction: Despite recommendations for influenza and COVID-19 vaccines, studies have documented gaps and disparities in vaccination coverage for adults and adolescents. Understanding the proportion and demographics of those unvaccinated against influenza and/or COVID-19 is important for tailoring appropriate messaging and strategies to increase confidence and uptake. Methods: Using the 2021 National Health Interview Survey (NHIS), we assessed the prevalence of four vaccination patterns (exclusive influenza vaccination, exclusive COVID-19 vaccination, dual influenza and COVID-19 vaccination, and neither vaccination) by sociodemographic and other characteristics among adults and adolescents 12–17 years. Adjusted multivariable regression analyses were conducted to examine factors associated with each of the four vaccination categories among adults and adolescents. Results: In 2021, 42.5% of adults and 28.3% of adolescents received both influenza and COVID-19 vaccines, while approximately a quarter (22.4%) of adults and a third (34.0%) of adolescents did not receive either vaccine. Among adults and adolescents, 6.0% and 11.4% were exclusively vaccinated against influenza and 29.1% and 26.4% were exclusively vaccinated against COVID-19, respectively. Among adults, exclusive COVID-19 or dual vaccination was more likely to be associated with older age, non-Hispanic multi/other race, and having a college degree compared to their respective counterparts. Exclusive influenza or neither vaccination was more likely to be associated with younger age, having a high school diploma or less, living below the poverty level, and having a previous COVID-19 diagnosis. Conclusion: During the COVID-19 pandemic, approximately two-thirds of adolescents and three-fourths of adults received exclusive influenza or COVID-19 vaccines or both vaccines in 2021. Vaccination patterns differed by sociodemographic and other characteristics. Promoting confidence in vaccines and reducing barriers to access is needed to protect individuals and families from severe health consequences of vaccine-preventable diseases. Being up-to-date with all recommended vaccinations can prevent a future resurgence of hospitalizations and cases. Key messages: 42.5% of adults and 28.3% of adolescents received both influenza and COVID-19 vaccines in 2021, while approximately a quarter (22.4%) of adults and a third (34.0%) of adolescents did not receive either vaccine; 6.0% of adults and 11.4% of adolescents were exclusively vaccinated against influenza and 29.1% of adults and 26.4% of adolescents were exclusively vaccinated against COVID-19. Among adults, exclusive COVID-19 vaccination or dual vaccination was more likely to be associated with older age, non-Hispanic multi/other race, and having a college degree or higher compared to their respective counterparts; exclusive influenza vaccination or neither vaccination was more likely to be associated with younger age, having a high school diploma or less, living below poverty level, and having a previous COVID-19 diagnosis compared to their respective counterparts. Promoting confidence in vaccines and reducing barriers to access is needed to protect individuals and families from severe health consequences of vaccine-preventable diseases. Being up-to-date with all recommended vaccinations can prevent a future resurgence of hospitalizations and cases, especially as new variants emerge.